Successful faecal microbiota transplant for recurrent Clostridium difficile infection delivered by colonoscopy through a diverted ileostomy in a patient with severe perianal Crohn's disease. (5th March 2018) - Digby-Bell, Jonathan; Williams, Andrew; Irving, Peter; Goldenberg, Simon
Abstract : We present the first reported case of successful treatment of recurrent Clostridium difficile infection with faecal microbiota transplantation delivered antegrade with a colonoscope through a diverting ileostomy.